CADD based designing and biological evaluation of novel triazole based thiazolidinedione coumarin hybrids as antidiabetic agent - Anchal Sharma; Anmol Narang; Nitish Kumar; Rupali Rana; Megha; Pooja; Muskan Dhir; Harmandeep Kaur Gulati; Jyoti; Aanchal Khanna; Jatinder Vir Singh; Sukhraj Kaur; et al. (Scientific Reports)
Abstract A series of 5-(substituted benzylidene) thiazolidine-2,4-dione and coumarin hybrids (I-1 to I-16) were designed and synthesized to explore key structural requirements for effective α-glucosidase inhibitors. Molecular docking studies were conducted to investigate their interactions with various targets, including DPP-4, α-glucosidase, α-amylase, and PPAR-γ. The docking scores and binding energies indicated that Compound I-1 emerged as the optimal scaffold for drug design, excluding α-amylase. Compound I-1 was synthesized based on the insights gained from molecular docking and simulations, which helped predict interactions and identify critical structural features. Pharmacokinetic properties were evaluated through drug-likeness and ADMET studies. Additionally, density functional theory (DFT) analyses were performed to assess the stability and reactivity of potential diabetes mellitus drug candidates. Dynamic simulation studies further elucidated the stability and interaction dynamics of the top-ranked compound I-1. In vitro evaluation against the α-glucosidase enzyme yielded an IC 50 value of 1.49 µg/ml. In vivo studies demonstrated that Compound I-1 significantly reduced blood glucose levels, with values of 94.15 mg/dL and 74.60 mg/dL at doses of 10 mg/kg and 20 mg/kg, respectively. Furthermore, Compound I-1, like Acarbose, resulted in significant reductions in ALT, AST, ALP, urea, LDH, and creatinine levels, suggesting improved liver and kidney function.